Права і свободи людини та інтереси держави як об’єкт публічно-сервісної діяльності Національної поліції України - Троян, В. А.; Troian, V. A. (Вісник Кримінологічної асоціації України. - 2017. - № 1 (15). - С. 229-239, 2017)
Розглянуто основні підходи до встановлення співвідношення категорій «права людини» та «свободи людини». Обґрунтовано взаємозалежність прав і свобод людини та інтересів держави як складових об’єкта публічно-сервісної діяльності Національної поліції України крізь призму предмета адміністративного права. Сформульовано визначення поняття «права і свободи людини та інтереси держави як об’єкт публічно-сервісної діяльності Національної поліції».

The main approaches in regard to the correlation of categories of “human rights” and “human freedoms” have been studied. The author has grounded the interdependence of human rights and the interests of the state as objects of public and service activities of the National police of Ukraine in the light of the subject of administrative law. Public and service activities of the National police have been offered to understand in the broad sense as normative;e determined activities of specially established state institution that aims to fulfill the tasks and functions of the state to ensure human rights and freedoms and to protect the interests of the society and the state, to maintain public order and security, to combat crime. If we consider the public and service activities of the National police in the narrow sense, then it is the activity aimed at providing public services in the sphere of public security and order, which is carried out at the request of individuals and legal entities and aimed at acquiring, changing or terminating the rights or duties in the respective field of public relations. It has been established that the public and service activities of the National police, being aimed at ensuring the realization and protection of human rights and freedoms as well as the interests of the state (having human rights and freedoms as well as the interests of the state as the objects) is the subject of administrative law, that is liable to administrative and legal regulation. It has been argued that human rights and freedoms as well as the interests of the state act both as objects of the public and service activities of the National police and objects of public relations arising in realizing the latter as the subject of administrative law. Human rights and freedoms as well as interests of the state as objects of public and service activities of the National police have been suggested to determine as the corresponding legal possibilities (degrees of freedom) of a human being that have to meet its own needs in regard to issuing consent document in the areas of licensing system, traffic, security activities and state interests in the spheres of national, environmental and economic security that act as objects of public relations as a subject of administrative law.

Рассмотрены основные подходы к выяснению соотношения категорий «права человека» и «свободы человека». Обосновано взаимозависимость прав и свобод человека и интересов государства как составляющих объекта публично-сервисной деятельности Национальной полиции Украины через призму предмета административного права. Сформулировано определение понятия «права и свободы человека и интересы государства как объект публично-сервисной деятельности Национальной полиции».
Human Rights And Freedoms As Well As State Interests As Objects Of Public And Service Activities Of The National Police
Права и свободы человека и интересы государства как объект публично-сервисной деятельности Национальной полиции Украины
Троян, В. А. Права і свободи людини та інтереси держави як об’єкт публічно-сервісної діяльності Національної поліції України / Вадим Анатолійович Троян // Вісник Кримінологічної асоціації України. - 2017. - № 1 (15). - С. 229-239.
Troyan, V. A. (2017), “Human rights and freedoms as well as state interests as objects of public and service activities of the National Police” [Prava i svobody liudyny ta interesy derzhavy yak ob’iekt publichno-servisnoi diialnosti Natsionalnoi politsii], Visnyk Kryminolohichnoi asotsiatsii Ukrainy, No. 1, pp. 229–239.
Keywords: Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; права і свободи людини; інтереси держави; Національна поліція України. National police of Ukraine. Национальная полиция Украины; публічно-сервісна діяльність; human rights and freedoms; human rights; state interests; National police of Ukraine; public service activities; права и свободы человека; интересы государства; Национальная полиция Украины; публично-сервисная деятельность